An assemblage of avatars: Digital organization as affective intensification in the GamerGate controversy. (September 2019) - Just, Sine N.
Through a study of the so-called GamerGate controversy, this article argues that a new dynamic of affective intensification is currently instating itself in the digital organization of not only highly collaborative industries, such as that of gaming, but of society as such. This dynamic may best be understood and conceptualized through reconsiderations of the notions of affective economies and affective labour. The affective constitution of digital organization is a process of affective intensification that not only works like an economy but is directly productive of economic value, and not only involves human emotionality but technological affectivity as well. Guided by the notions of assemblage, affordance and agency, the article offers a conceptual framework for studying affective intensification in and as socio-technical processes of value production.